2023
DOI: 10.1073/pnas.2220747120
|View full text |Cite
|
Sign up to set email alerts
|

Threatened North African seagrass meadows have supported green turtle populations for millennia

Abstract: “Protect and restore ecosystems and biodiversity” is the second official aim of the current UN Ocean Decade (2021 to 2030) calling for the identification and protection of critical marine habitats. However, data to inform policy are often lacking altogether or confined to recent times, preventing the establishment of long-term baselines. The unique insights gained from combining bioarchaeology (palaeoproteomics, stable isotope analysis) with contemporary data (from satellite tracking) identified ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 75 publications
1
3
0
Order By: Relevance
“…This study is also the first to use a large sample of archaeological green sea turtle bones, which are commonly recovered across the globe from coastal archaeological sites near locations where sea turtles have been harvested in the past. In that context, and alongside recent smaller scale studies (with a collective global total analyses of 39 green sea turtle bones [ 99 , 115 , 116 ]), our findings serve to underscore the value of archaeological green sea turtle bone assemblages as vast and almost untapped biomolecular archives for understanding past sea turtle behaviour. Given that many archaeological specimens date to a time before industrial-scale harvesting began, isotopic perspectives from these past sea turtle populations can offer valuable insights into ecological baseline shifts for conservation managers.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This study is also the first to use a large sample of archaeological green sea turtle bones, which are commonly recovered across the globe from coastal archaeological sites near locations where sea turtles have been harvested in the past. In that context, and alongside recent smaller scale studies (with a collective global total analyses of 39 green sea turtle bones [ 99 , 115 , 116 ]), our findings serve to underscore the value of archaeological green sea turtle bone assemblages as vast and almost untapped biomolecular archives for understanding past sea turtle behaviour. Given that many archaeological specimens date to a time before industrial-scale harvesting began, isotopic perspectives from these past sea turtle populations can offer valuable insights into ecological baseline shifts for conservation managers.…”
Section: Discussionsupporting
confidence: 73%
“…While still comparatively rare, over the last few years δ 34 S analyses have been increasingly applied among sea turtle research [81,[99][100][101][102][103][104][105]. Although some researchers have left observed δ 34 S variation uninterpreted, others have identified the utility of δ 34 S for distinguishing between green sea turtle foraging areas.…”
Section: Ecological and Conservation Relevancementioning
confidence: 99%
“…For instance, recent studies focusing on herbivores specializing in seagrass habitats observed consumer δ 13 C values that extend the higher-end boundaries for the known range for bone collagen of archaeological marine animals. Specifically, sea turtle bone collagen from the tropics had δ 13 C values up to ca –3.0‰ ([ 47 ] and up to –5.0‰ from the Mediterranean [ 48 ]), though latitudinal impacts on the δ 13 C of marine DIC [ 49 ] mean that an endpoint in temperate locations, such as our study region, would be 2–3‰ lower. In that context, while we therefore expect a degree of overlap in the potential δ 13 C range for bone collagen from consumers living in marine, estuarine and freshwater habitats (from the bottom end of the marine δ 13 C range up to about –9.0‰), values falling well above this threshold result from intensive use of seagrass habitats.…”
Section: Discussionmentioning
confidence: 99%
“…While archaeology has indeed much to offer to ongoing debates on species conservation and extinction, rewilding, the evolution of biodiversity and the dynamic interposition of human and earth systems in general [13,[18][19][20][21][22][23][24][25][26], the discipline has equally contributed to an overall dire outlook on the relationship between human agency and the biosphere [27][28][29][30]. Facing the recognition of human societies as the single major source of biodiversity attrition on the planet today [1,2,29,31,32], framing historically unprecedented 'Anthropocene' conditions [33][34][35][36][37] and novel ecosystems [38,39] that threaten the hospitality and habitability of the Earth as a whole [40], archaeologists have started to map similar processes and their origins in the past to show that the biodiversity crisis has deep-historical roots [17,18,29,[41][42][43][44][45][46][47]. These insights are crucial for contextualizing contemporary ecological challenges, but they may also invite the misleading conclusion that historical trajectories have been steered millennia ago, with little hope to intervene with or even correct them now.…”
Section: Introductionmentioning
confidence: 99%